1980
DOI: 10.1111/j.1600-0765.1980.tb00311.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parathyroid hormone on the numbers of nuclei in feline odontoclasts in vivo

Abstract: Odontoclasts exhibit varying numbers of nuclei. The purpose of the present study was to determine the effect of a low dose (4 USP units per 100 g. body weight) of parathyroid hormone extract (PTE) in vivo on the numbers of nuclei in whole feline odontoclasts. Odontoclasts were recovered in smear type preparations from the resorbing primary teeth of 12 kittens aged approximately 18 weeks. Four kittens had received PTE intravenously one hour prior to sacrifice, four six hours previously, and four were controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Under basal pH conditions, cultured feline osteoclasts were larger than human PMBC-derived osteoclasts unless stimulated by TGFb (Massey et al, 2001). Previous histological studies (Addison, 1979(Addison, , 1980 have shown that feline osteoclasts are larger than those from other species, of the order of 300 mm in diameter, with the number of nuclei often exceeding 100 (Allen et al, 1981;Ibbotson et al, 1984;Pharoah and Heersche, 1985). In contrast, osteoclasts isolated from neonatal mouse bone or grown in vitro are small and frequently have less than five nuclei.…”
Section: Discussionmentioning
confidence: 88%
“…Under basal pH conditions, cultured feline osteoclasts were larger than human PMBC-derived osteoclasts unless stimulated by TGFb (Massey et al, 2001). Previous histological studies (Addison, 1979(Addison, , 1980 have shown that feline osteoclasts are larger than those from other species, of the order of 300 mm in diameter, with the number of nuclei often exceeding 100 (Allen et al, 1981;Ibbotson et al, 1984;Pharoah and Heersche, 1985). In contrast, osteoclasts isolated from neonatal mouse bone or grown in vitro are small and frequently have less than five nuclei.…”
Section: Discussionmentioning
confidence: 88%
“…In pathological situations such as Paget’s disease, each OC has been shown to contain up to more than 100 nuclei [ 42 ]. Although human OCs in vitro can contain many nuclei in given experimental conditions, the vast majority of active OCs have 10 nuclei or less [ 38 , 43 , 44 ]. Several studies have shown that an increasing number of nuclei per OC results in an enhanced bone resorptive activity [ 17 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%